Articular and cutaneous nerve block at elbow: two cases report - Diwan,Sandeep (2020)
Abstract Background and objectives: In patients with elbow fractures, when there is suspected injury to underlying nerves, it is imperative for surgeons to elicit the function in the immediate postoperative period. Brachial plexus blocks like interscalene, supraclavicular and infraclavicular approaches can be a hurdle in such situations. The block planned should allow assessment of integrity of the nerves immediately in the postoperative period. Case report: We describe two cases in which we administered a block not yet described in literature. We blocked the cutaneous and articular branches innervating the elbow under ultrasound guidance. General anesthesia was administered in both cases. The block provided stable intraoperative hemodynamics, good postoperative analgesia and also allowed surgeons to test the viability of the nerve. Conclusion: In situations where nerves are injured during elbow fractures, selective articular cutaneous block at elbow can be used as it provides good perioperative analgesia, besides allowing evaluation of motor and sensory components in the postoperative period.